Peer review of the pesticide risk assessment of the active substance fenamiphos. (21st January 2019) - ; Abdourahime, Himdata; Anastassiadou, Maria; Arena, Maria; Auteri, Domenica; Barmaz, Stefania; Brancato, Alba; Brocca, Daniela; Bura, Laszlo; Carrasco Cabrera, Luis; Chiusolo, Arianna; Civitella, Consuelo; et al.
Abstract: The conclusions of EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State Greece and co‐rapporteur Member State Cyprus for the pesticide active substance fenamiphos are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012. The conclusions were reached on the basis of the evaluation of the representative uses of fenamiphos as a nematicide in fruiting vegetables (i.e. tomato, aubergine, cucumber, pepper and courgette), herbaceous ornamentals and in nursery stock (both perennial and herbaceous species). The reliable end points, appropriate for use in regulatory risk assessment are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.